School-Based Management Policy: A Dual-Approach Strategy for Enhancing School Quality - Wahyudi, Heri; Pratiwi, Sri Nurabdiah; Mahmood, Rosinah Binti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
The objectives of this study are to identify the type of School-Based Management (SBM) model implemented at Junior high schools, examine how environmental factors influence the implementation process, and evaluate the impact of SBM. This research focuses on the importance of policymakers' involvement and non-academic achievements, which remain underexplored. Using a qualitative case study approach, data were collected through interviews, observations, document analysis, and questionnaires. The study reveals three key findings. SBM was implemented through strategic planning that was aligned with national regulations and tailored to the school’s specific needs. Transformational leadership and participatory decision-making were central to fostering a collaborative school environment. The performance of the principal, teachers, and school committee contributed to achievements in both academic and non-academic domains, such as science olympiads, arts competitions, and sports tournaments. These findings suggest that integrating structured planning, inclusive leadership, and community participation enhances the overall quality of education. The research contributes to the discourse on effective SBM practices in urban schools and recommends the broader adoption of participatory and context-responsive strategies to support improvements in education quality.